Aligeydarova, Intizar - (:unkn) unknown (My University, 2026)
Intizar Khalil Aligeydarova graduated from the Faculty of English of Azerbaijan University of Languages in 1986, earning a degree in English and German Language Teaching. Since 1995, she has been a Senior Lecturer at the Department of Foreign Languages of the Azerbaijan University of Architecture and Construction. She has participated in numerous professional development programmes in English language teaching and methodology, including training supported by the Open Society Foundation between 2000 and 2005. Her research interests include English language teaching methodology, foreign language education, and applied linguistics. She is the author of 20 scientific articles, four course curricula, one textbook, and other educational and methodological publications.